Insights into the mechanism of growth and fat deposition by feeding different levels of lipid provided by transcriptome analysis of swamp eel (Monopterus albus, Zuiew 1793) liver - Zhang, Yazhou; Guo, Feng; Yang, Xin; Liu, Yu; Bao, Yihong; Wang, Zirui; Hu, Zhonghua; Zhou, Qiubai (Frontiers in Immunology, 2023)
The effects of feed lipid levels on swamp eel were studied. Essential functional genes were screened using transcriptomics. We divided 840 fish into seven groups (four replicates). A mixture of fish and soybean oils (1:4), 0%, 2%, 4%, 6%, 8%, 10%, and 12% was added to the basic feed were named groups one to seven (L1-L7), respectively. Isonitrogenous diets were fed swamp eel for 10 weeks. Growth performance, visceral index, nutritional components, and biochemical indexes were measured and analyzed. Livers of the 0%, 6%, and 12% groups were subjected to transcriptome sequencing analysis. In summary, (1) the suitable lipid level for the growth of swamp eel was 7.03–7.68%, (2) the crude fat content of whole fish, liver, intestine, muscle, and skin increased with the increase of lipid level, with some significant difference, and excess fat was deposited in skin tissue, (3) triglyceride, total cholesterol, and free fatty acid contents increased with the increase of feed lipid level. High-density lipoprotein levels in the L3 and L4 groups were higher than in the other groups. Blood glucose concentrations in the L5, L6, and L7 groups increased, (4) the liver tissue structure was damaged when the lipid level was too high, and (5) two-hundred-and-twenty-eight differentially expressed genes were found. In fish, several critical pathways regulating glucose metabolism and energy balance (e.g., glycerolipid metabolism, glycolysis synthesis, degradation of ketone bodies, and Janus Kinase/Signal Transducer and Activator of Transcription signaling pathway) were enriched compared with the Kyoto Encyclopedia of Genes and Genomes ( KEGG) database. Suitable lipid levels (7.03–7.68%) can promote the growth of swamp eel, and excessive lipid levels can cause elevated blood lipids and lead to liver cell damage. Regulatory mechanisms may involve multiple metabolic pathways for glucose and lipid metabolism in eels.